Leaf Morphology and Functional Traits of Four Mangrove Seedling Species Under Nursery Conditions - Lefdi Agung Nugraha; Pebriandi Pebriandi; Viny Volcherina Darlis; Muhammad Mardhiansyah; Ewi Irfani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Mangrove species exhibit variations in leaf functional traits that reflect differences in resource-use strategies; however, information on the coordination of these traits during the seedling stage remains limited. This study aimed to evaluate leaf functional trait variation among four mangrove species (Avicennia alba, Bruguiera gymnorrhiza, Bruguiera parviflora, and Rhizophora apiculata) by analyzing leaf economic traits, leaf morphological traits, and their interrelationships. A total of 120 seedlings grown under relatively uniform nursery conditions were evaluated. The measured traits included Specific Leaf Area (SLA), Leaf Dry Matter Content (LDMC), Aspect Ratio (AR), and Shrinkage Index (SI). Data were analyzed using descriptive statistics, one-way analysis of variance (ANOVA) followed by Duncan's Multiple Range Test (DMRT), and Principal Component Analysis (PCA). The results showed that all measured traits differed significantly among species (P < 0.05), with effect sizes ranging from moderate to very large. PCA revealed that the first two principal components explained 73.75% of the total variation in leaf traits, indicating that interspecific variation was driven by the coordination of multiple leaf traits rather than by a single trait. These findings demonstrate that a multivariate approach provides a more comprehensive understanding of leaf functional trait variation among mangrove seedlings.